Diseño de implementos didácticos con material reciclable para mejorar los procesos enseñanza-aprendizaje en el área de cultura física en la escuela “José Filomentor Cuesta” de patate viejo en el año lectivo 2011-2012. - Sopa Vivanco, Wilson Esteban (2013)
This research will be carried out in the province of Tungurahua, Canton Patate old village school " JOSÉ FILOMENTOR CUESTA” Patate old in the 2011-2012 school year "the same object will design tools and learning with recyclables creative use of waste that short and long term will improve students encouraging the correct orientation of the teaching-learning process. They are very obvious the profound and rapid changes that are taking place in all areas of society. Sport and physical activity, as recognized social activities, not escape this evolution and transformation. It is therefore essential that all professionals face up this stage Physical Culture without denying what is already there, looking for new targets, content and resources to provide as many opportunities as possible for people. The purpose of this design is to present various materials that have been reused through various waste materials and recovery for physical education area. Same as help you have a clear vision of the results you want to reach.